2020
DOI: 10.3390/jrfm13090208
|View full text |Cite
|
Sign up to set email alerts
|

Volatility in International Stock Markets: An Empirical Study during COVID-19

Abstract: Predicting volatility is a must in the finance domain. Estimations of volatility, along with the central tendency, permit us to evaluate the chances of getting a particular result. Financial analysts are frequently challenged with the assignment of diversifying assets in order to form efficient portfolios with a higher risk to reward ratio. The objective of this research is to analyze the influence of COVID-19 on the return and volatility of the stock market indices of the top 10 countries based on GDP using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
81
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 37 publications
13
81
0
3
Order By: Relevance
“…The two waves of COVID-19 infections had a not meaningful impact on the stock market volatility of Greece, Slovenia and the Baltic States which present low levels of real GDP per capita and stock market capitalisation to GDP (see Figure 3). The results on volatility about Germany, France and Italy confirm those of Chaudhary et al (2020) [5]. Moreover, findings support the leptokurtosis and asymmetry of stock daily returns.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The two waves of COVID-19 infections had a not meaningful impact on the stock market volatility of Greece, Slovenia and the Baltic States which present low levels of real GDP per capita and stock market capitalisation to GDP (see Figure 3). The results on volatility about Germany, France and Italy confirm those of Chaudhary et al (2020) [5]. Moreover, findings support the leptokurtosis and asymmetry of stock daily returns.…”
Section: Discussionsupporting
confidence: 87%
“…Shehzad et al(2020) concluded that "the European and the US markets are more affected by COVID-19 as compared to Asian markets" [25]. Chaudhary et al (2020) [5] employed the standard GARCH model to analyze the impact of the COVID-19 on the stock market indices of the top 10 countries based on GDP, and their results showed that, the COVID-19 pandemic increased the volatility of these indices. Using the GJR GARCH model, Bora and Basistha (2021) [26] investigated the impact of COVID-19 on the volatility of the two important stock market of India: Bombay Stock Exchange (BSE Sensex) and National Stock Exchange of India (NSE Nifty).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a group of studies has measured the impact of the COVID-19 pandemic on stock market performance in different countries. For instance, Chaudhry et al (2020) measured the effect of COVID-19 on the daily return volatilities of stock markets in the top ten countries based on GDP (the U.S., China, Japan, Germany, India, the U.K., France, Italy, Brazil, and Canada) between January 2019 and June 2020. They found a daily negative mean return for the aforementioned index between January 2020 and June 2020, which was characterized by its high volatility compared with normal periods.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…As such, nearly all the countries of Earth have implemented various containment measures, such as social distancing and lockdowns, in an effort to mitigate the pandemic's lethal impact. The top 10 countries based on GDP (the U.S., China, Japan, Germany, India, the U.K., France, Italy, Brazil, and Canada) have accounted for 60% of total cases as of 15 August 2020, which in turn halted many economic and financial activities across the globe (Chaudhry et al 2020). The stock market indices in the U.S., U.K., and China decreased by 14.9%, 21.4%, and 12.1% respectively (Shehzad et al 2020).…”
Section: Introductionmentioning
confidence: 99%